Alkali slag concrete specially suitable for low-temperature environment self-exothermic curing and preparation method thereof

By using self-exothermic curing alkali slag concrete in low-temperature environments, exothermic heat generation of sodium hydroxide dissolution reaction, calcium oxide hydration reaction and slag polymerization reaction, the problems of slowing down the early hydration rate of concrete and frost damage in low-temperature environments are solved, and efficient self-exothermic curing and improving mechanical properties are achieved.

CN119735416APending Publication Date: 2025-04-01ANHUI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411933752.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of low-temperature building materials, and particularly relates to self-heat-release curing alkali slag concrete specially suitable for a low-temperature environment and a preparation method of the self-heat-release curing alkali slag concrete. The alkali slag concrete is prepared from the following raw materials in parts by weight: 350 to 450 parts of slag, 50 to 150 parts of calcium oxide, 22.5 to 40 parts of sodium hydroxide, 10 parts of silica fume, 225 to 250 parts of water, 130 to 150 parts of liquid silicon, 0.05 to 0.1 part of sulfuric acid, 600 to 650 parts of sand and 1000 to 1200 parts of gravel. Through sodium hydroxide dissolution reaction heat release, calcium oxide hydration reaction heat release and slag polymerization reaction heat release, under the normal curing condition, self-heat-release curing in a low-temperature environment can be achieved, heat preservation protection and use of an anti-freezing agent needed by concrete construction in winter are avoided, the concrete curing mode in winter is simplified, the construction progress is accelerated, and the construction cost is reduced. And manpower and material resource costs are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of low-temperature building materials, and in particular relates to a self-exothermic curing alkali slag concrete specially suitable for low-temperature environments and a preparation method thereof. Background Art

[0002] my country has a vast territory, spanning five climate zones: severe cold, cold, hot summer and cold winter, hot summer and warm winter, and temperate. Among them, cold or severe cold areas account for more than 70% of my country's land area. In cold areas, the average temperature of the coldest month is -10-0℃, and the number of days with an average daily temperature of ≤5℃ is 90-145d; while in severe cold areas, the average temperature of the coldest month is ≤-10℃, and the number of days with an average daily temperature of ≤5℃ is ≥145d. As a pillar material in construction engineering, concrete plays an extremely important role in winter construction. Therefore, it is increasingly important to ensure the safety and reliability of concrete engineering in cold environments and improve the key technologies and theoretical basis for winter construction. There are two important differences between winter construction concrete and normal temperature construction concrete: first, the lower ambient temperature greatly reduces the early cement hydration rate, and the strength development is slow or even stagnant; second, when the temperature is too low, the liquid phase in the concrete freezes, and this process causes a volume expansion of nearly 9%, which can produce huge frost heave stress. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention proposes a self-exothermic curing alkali-slag concrete and a preparation method specifically suitable for low-temperature environments; the difficulty of promoting rapid hydration of cementitious materials in low-temperature environments is overcome, freezing damage is avoided, and the continuous development of the strength of concrete materials is ensured.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A kind of alkali slag concrete specially suitable for self-exothermic curing in low temperature environment, the proportion of raw materials for its preparation is:

[0006] 350-450 parts of slag,

[0007] 50-150 parts of calcium oxide,

[0008] Sodium hydroxide 22.5-40 parts,

[0009] 10 parts of silica fume,

[0010] 225-250 parts of water,

[0011]

[0012] Furthermore, the alkali-slag concrete is applicable to a temperature of -30°C to 0°C.

[0013] Furthermore, the main components of the slag are: SiO2 55-60%, Al2O3 11-15%, Fe2O3 7-10%, CaO 0.1-0.5%, MgO 0.3-0.5%, and the loss on ignition is 1.3-1.5%.

[0014] Furthermore, the concentration of the sulfuric acid is 90-95%.

[0015] Furthermore, the thickener is a mixture of hydroxyethyl cellulose, polyvinyl alcohol and polyacrylamide in a weight ratio of 1:(2-5):1.

[0016] A method for preparing alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment, the preparation method comprising the following steps:

[0017] S1. Slowly add sulfuric acid into liquid silicon, add a colloidal protective agent and a colloidal stabilizer, and stir evenly to prepare a nano-SiO2 precursor solution;

[0018] S2. Evenly mix slag, calcium oxide, silica fume and sodium hydroxide in a mixer, then add water, nano-SiO2 precursor solution and sand and stir evenly, then add crushed stone and thickener and stir to obtain alkali slag concrete material for pouring.

[0019] Furthermore, the sodium hydroxide needs to be ball-milled before mixing so that the particle size of the sodium hydroxide particles is 0.1 to 0.5 mm.

[0020] Furthermore, the colloidal protective agent is polyamide particles, and the dosage of the colloidal protective agent is 1% of liquid silicon.

[0021] Furthermore, the colloid stabilizer is polyethylene particles, and the dosage of the colloid stabilizer is 0.5% of liquid silicon.

[0022] Beneficial effects of the present invention:

[0023] 1. The present invention can realize self-heating curing in a low-temperature environment under normal curing conditions through the heat release of sodium hydroxide dissolution reaction, heat generation of calcium oxide hydration reaction and heat release of slag polymerization reaction, thereby avoiding the use of thermal insulation protection and antifreeze agents required for winter concrete construction, simplifying the winter concrete curing method, accelerating the construction progress and reducing manpower and material costs.

[0024] 2. The present invention realizes the early strength and high strength of alkali slag concrete materials through component modification and regulation, composite excitation strengthening and multi-product synergistic modification and enhancement. The compressive strength reaches 40MPa after curing for 1 day, which significantly improves the mechanical properties, completely eliminates the influence of low temperature frost damage of concrete, and realizes the casting of alkali slag concrete materials in low temperature environment.

[0025] 3. The present invention enhances the nucleation sites generated by nano-silicon dioxide, so that the alkali slag concrete can develop normal mechanical properties even at low temperatures or even in ultra-low temperature environments (cement concrete cannot be poured below 5°C, and the strength of cement concrete no longer develops below 0°C). This truly realizes an alkali slag concrete material that is not affected by the low temperature environment and is specifically suitable for construction in a low temperature environment. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Preparation of thickener: 1 kg of hydroxyethyl cellulose, 5 kg of polyvinyl alcohol and 1 kg of polyacrylamide were mixed together to prepare a thickener.

[0029] The first purpose of the present invention is to provide a material formula for step-by-step self-exothermic curing of alkali-slag concrete, which can maintain the internal curing temperature of alkali-slag concrete within 24 hours, and a composite water-borne self-exothermic curing material with calcium oxide and slag as main raw materials and sodium hydroxide as an activator.

[0030] A method for preparing alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment, the preparation method comprising the following steps:

[0031] S1. Slowly add sulfuric acid into liquid silicon, add a colloidal protective agent and a colloidal stabilizer, and stir evenly to prepare a nano-SiO2 precursor solution;

[0032] S2. Evenly mix slag, calcium oxide, silica fume and sodium hydroxide in a mixer, then add water, nano-SiO2 precursor solution and sand and stir evenly, then add crushed stone and thickener and stir to obtain alkali slag concrete material for pouring.

[0033] Sodium hydroxide needs to be ball-milled before mixing so that the particle size of the sodium hydroxide particles is 0.1 to 0.5 mm;

[0034] The colloidal protective agent is polyamide particles, and the amount of the colloidal protective agent is 1% of liquid silicon;

[0035] The colloid stabilizer is polyethylene particles, and the dosage of the colloid stabilizer is 0.5% of liquid silicon.

[0036] Embodiment 1-4:

[0037] The present invention proposes a kind of alkali slag concrete which is suitable for self-heating curing in low temperature environment. The raw material proportions are different in the temperature range of -20℃-10℃. The specific raw material proportions in the temperature range of -20℃-10℃ are shown in Table 1:

[0038] Table 1 Self-exothermic material ratio unit kg / m 3

[0039]

[0040] Note: The dosage is linearly inserted between -30℃ and 0℃

[0041] Performance Test:

[0042] The performance test of the alkali slag concrete materials prepared in Examples 1 to 4 was carried out, and the specific test results are as follows:

[0043] Self-exothermic effect detection: The self-exothermic gelling material is composed of the activator sodium hydroxide, the alkali-activated raw material calcium oxide and slag. Sodium hydroxide is pre-milled into micro powder (particle fineness is less than 0.5mm), and mixed evenly with slag and calcium oxide. When preparing the test piece, first add the mixed material into the stirring pot, add experimental water and stir (1-2 minutes), ensure that the amount of sodium hydroxide dissolved is between 40% and 60%, and control the dissolution of sodium hydroxide to achieve primary heat release. Then add sand and gravel, and stir for another 1-1.5 minutes to complete the preparation. Ensure that the amount of sodium hydroxide dissolved is between 80% and 100%, use the heat of the primary heat release to accelerate the hydration reaction of calcium oxide to achieve secondary heat release, and finally use the heat of the secondary heat release to promote the polymerization reaction of slag to achieve tertiary heat release, and make full use of the first, second and third heat releases to achieve the self-exothermic curing problem of alkali slag concrete. The specific curing effect is shown in Table 2.

[0044] Table 2 Temperature change inside the cubic specimen Unit: °C

[0045]

[0046] Note: The cubic specimen is 100mm×100mm×100mm

[0047] Embodiment 5-8:

[0048] In order to achieve component modification and regulation, composite excitation strengthening and multi-product synergistic modification and enhancement, and make the compressive strength of alkali slag concrete reach 40MPa within 24 hours, this application uses slag, calcium hydroxide (formed by calcium oxide hydration reaction), liquid sodium silicate and silica fume mixed materials to achieve the optimal calcium-silicon ratio and effectively promote early strength development; through component modification and regulation (ratio see Table 3). The cementitious material is composed of slag, calcium oxide and silica fume, which account for 68%-88%, 10%-30% and 2% of the cementitious material respectively. The optimal ratio of slag, calcium oxide and silica fume accounts for 85%, 13% and 2% of the cementitious material, and then the compressive strength at different ages is measured.

[0049] Table 3 Component modification and regulation ratio Unit: kg / m 3

[0050]

[0051] Note: The dosage is linearly inserted between -30℃ and 0℃

[0052] Performance test: The alkali slag concrete materials prepared in Examples 5 to 8 were subjected to performance tests. The specific test results are shown in Table 4:

[0053] Table 4 Component modified compressive strength unit MPa

[0054]

[0055] Note: The dosage is linearly inserted between -30℃ and 0℃

[0056] Combining the data in Table 4, it can be seen that the compressive strength is different at different temperatures; this is because the hydroxide ions of calcium hydroxide formed by the hydration of calcium oxide can play a role in maintaining a high alkaline environment, while the remaining calcium ions can play a multi-product synergistic modification and early strength effect. This is because the formation of hydrated calcium silicate and calcium aluminosilicate gel is inseparable from the polymerization of active calcium. The active calcium in calcium hydroxide can combine with the active silicon and aluminum in the slag and liquid silicon to form a polymerization product, thereby playing a multi-product synergistic modification and early strength effect, further improving the early compressive strength.

[0057] Comparative Example 1: Compared with Example 5, the calcium oxide content in Comparative Example 1 is 0, and the sodium hydroxide content is 20 kg / m 3 .

[0058] The pH of the composite excitation specimens prepared in Examples 5 to 8 and Comparative Example 1 was measured. The results are shown in Table 5.

[0059] Table 5 pH changes in the center of the composite excitation specimen

[0060]

[0061] Note: The pH value of the center of the specimens of different ages is tested by rotating the hole to take the powder.

[0062] Combined with the data in Table 5, it can be seen that as time goes by, the alkalinity of the composite excitation specimen in Comparative Example 1 is significantly weakened; this is because calcium oxide generates calcium hydroxide while releasing heat to achieve self-curing through hydration reaction. The polymerization reaction of alkali-excited materials is carried out in a strong alkaline excitation environment established by sodium hydroxide, and strong alkali is a key factor in promoting the dissolution and re-condensation of active substances. As the alkali-excited polymerization reaction proceeds, the hydroxide ions provided by sodium hydroxide are gradually consumed and lost, and the formed calcium hydroxide effectively compensates for the continuous consumption of hydroxide ions, maintains a high alkaline environment, exerts a composite excitation strengthening effect, improves the polymerization reaction efficiency, and promotes the efficient formation of polymerization products, thereby ensuring that the alkali slag concrete material has early strength and high strength characteristics.

[0063] Embodiment 9-12:

[0064] The third object of the present invention is to provide a nano-silica nucleation site enhancement method that can promote the normal polymerization reaction and strength development of alkali-activated slag materials under low temperature conditions. Through the formation and dispersion of nucleation sites, more growth points can be provided for the formation of polymerization products, effectively preventing the in-situ coverage of polymerization products, thereby promoting the strength development of alkali-activated slag in a low-temperature environment.

[0065] The raw material ratios in Examples 9-12 are different from those in Examples 1-4 mainly in the ratios of water, liquid silicon and sulfuric acid at different temperatures, and the ratios of other raw materials are the same as those in Examples 1-4 at different temperatures; the ratios of water, liquid silicon and sulfuric acid at different temperatures in Specific Examples Examples 9-12 are shown in Table 6:

[0066] Table 6 Component modification and regulation ratio Unit: kg / m 3

[0067]

[0068]

[0069] To achieve the third purpose, the precursor solution generated in the nano-SiO2 is a prefabricated solution in which the nano-SiO2 particles have not yet precipitated. After being added to the alkali-slag slurry, the SiO2 in the solution precipitates in the form of nanoparticles and is evenly dispersed in the alkali-slag slurry. This method has a simple preparation process and low cost. It can not only completely eliminate the agglomeration problem of nanopowders and the problem that the in-situ covering of the polymerization product hinders the continuous reaction, but also greatly improve the mechanical properties of nanomaterials on alkali-slag materials, and promote the rapid development of the mechanical properties of alkali-slag concrete in low-temperature environments.

[0070] If nanomaterials are simply mixed with alkali-activated materials, sand, gravel and other dry materials to prepare nano-modified alkali-activated concrete, the nanomaterials are prone to agglomeration. This not only fails to fully exert the role of the nanomaterials, but also the agglomerated nanomaterial particles often form defects in the alkali-activated concrete, thereby reducing the strength and durability of the concrete.

[0071] First, strong alkaline silica sol, colloidal protective agent and colloidal stabilizer are used, and then a nano-SiO2 precursor solution can be obtained through a specific process. This solution is a solution in which nano-SiO2 particles have not yet precipitated. After adding it to the alkali-activated slurry, the SiO2 in the solution precipitates in the form of nanoparticles and is evenly dispersed in the alkali-activated slurry.

[0072] First, sulfuric acid is slowly mixed into liquid silicon and stirred evenly at high speed with a blender to stimulate some silica gel ions to react and form (0%-20%), but not yet solidified. They are immediately added to the slag slurry for preparation, and the remaining silica gel ions are crystallized and precipitated through alkali-induced reaction (20%-80%).

[0073] in conclusion:

[0074] 1. Through the heat release of sodium hydroxide dissolution reaction, calcium oxide hydration reaction and slag polymerization reaction, under normal curing conditions, self-heating curing in low temperature environment can be achieved, avoiding the use of thermal insulation and antifreeze required for winter concrete construction, simplifying the winter concrete curing method, speeding up the construction progress and reducing manpower and material costs.

[0075] 2. Through the modification and regulation of components, composite excitation strengthening and multi-product synergistic modification and enhancement, the early strength and high strength of alkali slag concrete materials are achieved, and the compressive strength reaches 40MPa after 1d of curing, which significantly improves the mechanical properties, completely eliminates the impact of low temperature frost damage on concrete, and realizes the casting of alkali slag concrete materials in a low temperature environment.

[0076] 3. Through the modification and enhancement of the nucleation sites generated by nano-silicon dioxide, the alkali slag concrete can develop its mechanical properties normally even at low temperatures or even in ultra-low temperature environments (cement concrete cannot be poured below 5°C, and the strength of cement concrete no longer develops below 0°C). This is truly an alkali slag concrete material that is not affected by the low temperature environment and is specifically suitable for construction in low temperature environments.

[0077] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0078] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A kind of alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment, characterized in that: The ratio of its preparation raw materials is:

2. The alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment according to claim 1, characterized in that: The alkali slag concrete is applicable to a temperature of -30°C to 0°C.

3. The alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment according to claim 1, characterized in that: The main components of the slag are: SiO2 55-60%, Al2O3 11-15%, Fe2O3 7-10%, CaO 0.1-0.5%, MgO 0.3-0.5%, and the ignition loss is 1.3-1.5%.

4. The alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment according to claim 1, characterized in that: The concentration of the sulfuric acid is 90-95%.

5. The alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment according to claim 1, characterized in that: The thickener is prepared by mixing hydroxyethyl cellulose, polyvinyl alcohol and polyacrylamide in a weight ratio of 1:(2-5):

1.

6. A method for preparing alkali-slag concrete suitable for self-exothermic curing in low temperature environment as claimed in claim 1, characterized in that: The preparation method comprises the following steps: S1. Slowly add sulfuric acid into liquid silicon, add a colloidal protective agent and a colloidal stabilizer, and stir evenly to prepare a nano-SiO2 precursor solution; S2. Evenly mix slag, calcium oxide, silica fume and sodium hydroxide in a mixer, then add water, nano-SiO2 precursor solution and sand and stir evenly, then add crushed stone and thickener and stir to obtain alkali slag concrete material for pouring.

7. The alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment according to claim 6, characterized in that: The sodium hydroxide needs to be ball-milled before mixing so that the particle size of the sodium hydroxide particles is 0.1 to 0.5 mm.

8. The alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment according to claim 6, characterized in that: The colloidal protective agent is polyamide particles, and the dosage of the colloidal protective agent is 1% of liquid silicon.

9. The alkali-slag concrete specially suitable for self-exothermic curing in low temperature environment according to claim 6, characterized in that: The colloid stabilizer is polyethylene particles, and the dosage of the colloid stabilizer is 0.5% of liquid silicon.